Dissecting the effects of preconditioning with inflammatory cytokines and hypoxia on the angiogenic potential of mesenchymal stromal cell (MSC)-derived soluble proteins and extracellular vesicles (EVs). (February 2021) - Gorgun, Cansu; Ceresa, Davide; Lesage, Raphaelle; Villa, Federico; Reverberi, Daniele; Balbi, Carolina; Santamaria, Sara; Cortese, Katia; Malatesta, Paolo; Geris, Liesbet; Quarto, Rodolfo; Tasso, Roberta
Abstract: Mesenchymal stromal cells (MSCs) are characterized by a regulatory phenotype and respond promptly to the environmental signals modulating their secretory activity. An appropriate preconditioning may induce MSCs to release secretomes with an enhanced regenerative potential. However, it fails to take into account that secretomes are composed by both soluble factors and extracellular vesicles (EVs), whose functions could be altered differently by the preconditioning approach. Here we demonstrate that the MSC secretome is strongly modulated by the simultaneous stimulation with hypoxia and pro-inflammatory cytokines, used to mimic the harsh environment present at the site of injury. We observed that the environmental variations strongly influenced the angiogenic potential of the different secretome fractions. Upon inflammation, the pro-angiogenic capacity of the soluble component of the MSC secretome was strongly inhibited, regardless of the oxygen level, while the EV-encapsulated component was not significantly affected by the inflammatory stimuli. These effects were accompanied by the modulation of the secreted proteins. On one hand, inflammation-activated MSCs release proteins mainly involved in the interaction with innate immune cells and in tissue remodeling/repair; on the other hand, when MSCs are not exposed to an inflamed environment, they respond to the different oxygen levels modulating the expression of proteins involved in the angiogenic process. The cargo content (in terms of miRNAs) of the corresponding EV fractions was less sensitive to the influence of the external stimuli. Our findings suggest that the therapeutic efficacy of MSC-based therapies could be enhanced by selecting the appropriate preconditioning approach and carefully discriminating its effects on the different secretome components.